1995
DOI: 10.1002/cne.903560405
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide tyrosine in the brain of the African lungfish, Protopterus annectens: Immunohistochemical localization and biochemical characterization

Abstract: Lungfishes, which share similarities with both fishes and amphibians, represent an interesting group in which to investigate the evolutionary transition from fishes to tetrapods. In the present study, we have investigated the localization and biochemical characteristics of neuropeptide Y (NPY)-immunoreactive material in the central nervous system of the African lungfish, Protopterus annectens. NPY-immunoreactive cell bodies were found in various regions of the brain, most notably in the telencephalon (septal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 83 publications
6
19
0
Order By: Relevance
“…In the rat hypothalamus, intragranular costorage of NPY and arginine vasopressin in the paraventricular magnocellular neurons was reported, strongly suggesting that the paraventricular nucleus is an origin of the NPY-ir fibers found in the hypophysis [Kagotani et al, 1990]. In the teleosts [Subhedar et al, 1996] and lungfish [Vallarino et al, 1995], the preoptic nucleus includes NPY-ir cells, whereas no NPY-ir cells were demonstrated in the preoptic nuclei of African clawed toad [Tunihof et al, 1994], dogfish [Chiba and Honma, 1992], sturgeon [Chiba and Honma, 1994], and bichir [Chiba, 1997]. Origin(s) of the NPY-ir fibers in the lamprey neurohypophysis should be experimentally analyzed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat hypothalamus, intragranular costorage of NPY and arginine vasopressin in the paraventricular magnocellular neurons was reported, strongly suggesting that the paraventricular nucleus is an origin of the NPY-ir fibers found in the hypophysis [Kagotani et al, 1990]. In the teleosts [Subhedar et al, 1996] and lungfish [Vallarino et al, 1995], the preoptic nucleus includes NPY-ir cells, whereas no NPY-ir cells were demonstrated in the preoptic nuclei of African clawed toad [Tunihof et al, 1994], dogfish [Chiba and Honma, 1992], sturgeon [Chiba and Honma, 1994], and bichir [Chiba, 1997]. Origin(s) of the NPY-ir fibers in the lamprey neurohypophysis should be experimentally analyzed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical data for NPY-ir innervation in the hypophyses of the following fish groups have been reported: Elasmobranchii [Vallarino et al, 1988;Chiba and Honma, 1992], Chondrostei [Chiba and Honma, 1994], Polypteriformes [Chiba, 1997], Dipnoi [Vallarino et al, 1995], and Teleostei [Pontet et al, 1989;Batten et al, 1990;Danger et al, 1991;Vecino and Ekström, 1992;Magliulo-Cepriano and Schreibman, 1993;Chiba et al, 1996;Subhedar et al, 1996]. However, in Agnatha, the NPY-ir innervation in the hypophysis is indistinct or negligible in the brown hagfish [Chiba et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lungfish thus represent a group of particular interest in which to investigate the evolutionary transition between fish and tetrapods (Romer, 1966;Miles, 1977;Rosen et al, 1981). We have previously described the distribution of NPY-containing neurons in the brain of the African lungfish Protopterus annectens, and we have shown the occurrence of numerous cell bodies and fibers in the hypothalamus (Vallarino et al, 1995b). In contrast, to our knowledge, the mapping of GABA-containing neurons has not yet been determined in the CNS of Dipnoans.…”
mentioning
confidence: 89%
“…We have previously shown that the preoptic nucleus of P. annectens possesses several populations of neurons containing different neuropeptides, including ␣-MSH (Vallarino et al, 1992), gonadotropin-releasing hormone (King et al, 1995), FMRFamide (Vallarino et al, 1995a), NPY (Vallarino et al, 1995b), atrial natriuretic factor (Vallarino et al, 1996), somatostatin (Vallarino et al, 1997), and enkephalins . In the course of the present study, we have noticed that the distribution of GAD-positive perikarya in the periventricular preoptic nucleus overlaps that described for NPY-immunoreactive neurons.…”
Section: Colocalization Of Gad and Npy-like Immunoreactivity In The Pmentioning
confidence: 99%